The effects of interest rate on GDP growth and inflation rate using structural vector auto regressive (SVAR) model for Myanmar economy - Myint, Ohn Mar
Abstract (The agenda-setting framework formulated by Mccombs and Shaw (1972) describes the ability of media organizations
May 2017.
Thesis (M.S. Statistics)--University of the Philippines, Diliman.
Keywords: Econometrics; Forecasting; Growth Domestic Product